2004
DOI: 10.1161/01.cir.0000109691.16944.da
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Prognostic Impact of Heart Failure Complicating Acute Coronary Syndromes

Abstract: Background— Few data are available on the impact of heart failure (HF) across all types of acute coronary syndromes (ACS). Methods and Results— The Global Registry of Acute Coronary Events (GRACE) is a prospective study of patients hospitalized with ACS. Data from 16 166 patients were analyzed: 13 707 patients without prior HF or cardiogenic shock at presentation were identified. Of these, 1778 (13%) had an admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
2
8

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 473 publications
(158 citation statements)
references
References 25 publications
(24 reference statements)
6
129
2
8
Order By: Relevance
“…[3][4][5][6][7] It is estimated that 20 to 40% of patients with AMI will develop HF. 3,4,7 Patients post AMI with HF and/or LVSD have a 3-to 4-fold increased risk of in-hospital death, as well as significant increases in 30-day mortality, long-term mortality, and rehospitalization rates compared with patients with AMI and without HF.…”
Section: The Burden Of Post-acute Myocardial Infarction Heart Failurementioning
confidence: 99%
See 3 more Smart Citations
“…[3][4][5][6][7] It is estimated that 20 to 40% of patients with AMI will develop HF. 3,4,7 Patients post AMI with HF and/or LVSD have a 3-to 4-fold increased risk of in-hospital death, as well as significant increases in 30-day mortality, long-term mortality, and rehospitalization rates compared with patients with AMI and without HF.…”
Section: The Burden Of Post-acute Myocardial Infarction Heart Failurementioning
confidence: 99%
“…[3][4][5][6][7] It is estimated that 20 to 40% of patients with AMI will develop HF. 3,4,7 Patients post AMI with HF and/or LVSD have a 3-to 4-fold increased risk of in-hospital death, as well as significant increases in 30-day mortality, long-term mortality, and rehospitalization rates compared with patients with AMI and without HF. [3][4][5][6] Recently, it has been shown that the first 30 days post infarction is the period of highest risk in patients with LVSD, especially for sudden cardiac death (Fig.…”
Section: The Burden Of Post-acute Myocardial Infarction Heart Failurementioning
confidence: 99%
See 2 more Smart Citations
“…1 The presence of HF in the patient post AMI greatly increases the risk for adverse clinical outcomes. The development of HF is associated with a significantly higher mortality during hospitalization for AMI, 2,3 at 30 days post AMI, 1 and at 6 months after discharge. 2 In addition, patients with HF have increased lengths of hospital stay for AMI by approximately 2 days and a greater readmission rate than patients without HF.…”
Section: Introductionmentioning
confidence: 99%